2021
DOI: 10.3390/su13084328
|View full text |Cite
|
Sign up to set email alerts
|

A Pathway for Sustainable Agriculture

Abstract: Expanding populations, the impacts of climate change, availability of arable land, and availability of water for irrigation collectively strain the agricultural system. To keep pace and adapt to these challenges, food producers may adopt unsustainable practices that may ultimately intensify the strain. What is a course of technological evolution and adoption that can break this cycle? In this paper we explore a set of technologies and food production scenarios with a new, reduced-order model. First the model i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 26 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…It is worrisome that global statistics show that the irrigation systems with a higher WEF nexus performance, i.e. micro-irrigation are the least used (5% of agricultural land) than sprinkler (20% of agricultural land) and surface (75% of agricultural land) which have relatively lower WEF nexus performance (AL-agele et al 2021 ). This excludes the irrigators from LICs, e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worrisome that global statistics show that the irrigation systems with a higher WEF nexus performance, i.e. micro-irrigation are the least used (5% of agricultural land) than sprinkler (20% of agricultural land) and surface (75% of agricultural land) which have relatively lower WEF nexus performance (AL-agele et al 2021 ). This excludes the irrigators from LICs, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…According to ADB ( 2017 ) and AL-agele et al ( 2021 ), pressure is growing on resources. The world must reduce the inputs used per unit of crop produced, for example, by installing efficient drip and sprinkler irrigation systems (FAO 2011 ).…”
Section: Conceptual Framework and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…In light of this, the role of agriculture should be underlined, as it is the world's major water consumer, reaching a consumption of up to 90% of the total water supplies in some areas, with this figure expected to worsen in many places [3][4][5][6][7]. Agriculture is also of crucial importance with regard to climate change, one of the greatest threats to both humans and the environment; in addition to its high vulnerability because of extreme and unpredicted weather conditions that increase water scarcity, agriculture contributes up to 14% of greenhouse gas emissions [8][9][10][11][12]. Against this background and taking into account the inherent relationship between water and land use, agriculture plays a key role in the global task of guaranteeing water supply from a sustainability perspective [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Ayars et al [4] reviewed a series of subsurface drip irrigation case studies that showed increased yield and crop quality, and reduced water application, weed control, fertilization, and tillage relative to surface irrigation. These efficiency gains lead to increased agriculture production and reduced water loss, and they follow the irrigation innovation technology pathway toward agriculture sustainability [5,6].…”
Section: Introduction 1backgroundmentioning
confidence: 99%